2016
DOI: 10.1093/ehjci/jew212
|View full text |Cite
|
Sign up to set email alerts
|

CT sizing for left atrial appendage closure is associated with favourable outcomes for procedural safety

Abstract: In this single-centre registry of LAA closure, routine incorporation of CT was associated with excellent outcomes for procedural safety and absence of major residual leak. Mean orifice size may be preferable to maximum orifice size. A particular value of CT may be the detection and subsequent avoidance of gross sizing error by 2D TOE that occurs in a small but important proportion of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 17 publications
4
54
0
3
Order By: Relevance
“…Our findings are consistent with previous comparisons of CT angiography to TEE for measuring LAA size, and provide further evidence that TEE has limitations in providing accurate size measurements . For the most part, TEE does allow acceptable sizing in terms of LAA ostial diameter and depth for successful completion of LAA occlusion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are consistent with previous comparisons of CT angiography to TEE for measuring LAA size, and provide further evidence that TEE has limitations in providing accurate size measurements . For the most part, TEE does allow acceptable sizing in terms of LAA ostial diameter and depth for successful completion of LAA occlusion.…”
Section: Discussionsupporting
confidence: 89%
“…Transesophageal echocardiography (TEE) is currently employed as the standard for procedural measurement of the LAA ostial diameter and depth in the two‐dimensional (2D) omniplane views of 0°, 45°, 90°, and 135°. Studies comparing TEE sizing of the LAA with computed tomography (CT) imaging have shown more accurate LAA ostial diameter and depth with CT compared to TEE . However, routine use of CT is not commonly performed commercially due to lack of formal vendor recommendation, and is not feasible for every case at every institution due to workflow, cost, reimbursement, and the need for intravenous contrast.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Berti et al showed that preprocedural CT was associated with a shorter fluoroscopy time, less frequent need for a second device, and less pericardial tamponade. Moreover, other small reports suggest that CT may provide a more accurate measurement of the LAA and that LAA size is frequently underestimated when assessed by TOE …”
Section: Discussionmentioning
confidence: 99%
“…Rajwani et al. used a preprocedural MDCT to measure the LAA orifice size for Watchman device size selection . Saw et al.…”
Section: Discussionmentioning
confidence: 99%